Students' Technology, Cognitive, and Content Knowledge (TSCCK) Instructional Model Effect on Cognitive Load and Learning Achievement - Qiong Wu; Sirirat Petsangsri; John Morris (MDPI AG, 2022)
The application of scientific and technological approaches in education has been increasing year by year. We evaluated the effect of a TSCCK model based on the cognitive load theory on the cognitive load and learning achievement of vocational students: this model had six components: (1) analysis; (2) content development; (3) cloud development; (4) learning activity development; (5) model implementation; and (6) model revision. We used 62 students randomly selected from 115 students taking an "E-commerce data analysis and processing" course and used cluster random sampling. A total of 31 students were taught with instructions based on the TSCCK model, while 31 students were taught with a traditional method. The instruments used included lesson plans for the TSCCK group developed using the cognitive load theory and the workload profile self-rating scale (WP scale) used to measure the student cognitive load for both groups. The students who learned with TSCCK had significantly lower cognitive load (WP scale) scores than the students who learned with the traditional method, and their achievement scores were higher. The MANOVA confirmed that both the achievement scores and cognitive load measures for the two groups were significantly different at the 0.05 level.